The Relationship between Credit Volume and Non-performing Loans on Profitability Levels - Muhammad Ashary Anshar (Advances in Management & Financial Reporting, 2023)
This study aims to determine the relationship between the volume of credit and the level of profitability and the relationship between non-performing loans and the level of profitability at PT. Bank Rakyat Indonesia (Persero) Tbk. Makassar Ahmad Yani branch was researched for the last 5 (five) years, namely 2010-2014. The analytical method used in this research is the descriptive analysis method, statistical analysis of correlation, and determination using primary data obtained directly from PT. Bank Rakyat Indonesia (Persero), Tbk Makassar Branch Ahmad Yani. Based on the results of research conducted, an increase in the volume of credit tends to increase the profitability of PT. Bank Rakyat Indonesia (Persero), Tbk Makassar Branch Ahmad Yani. Meanwhile, non-performing loans and the level of profitability have a negative relationship. This means that when non-performing loans increase, the level of profitability will be low. On the other hand, when non-performing loans decrease, profitability will increase.